ANALYSIS OF SCIENCE PROCESS SKILLS AND SCIENTIFIC ATTITUDES JUNIOR HIGH SCHOOL STUDENTS IN NUNUKAN REGENCY - Buhera, Rusdiman; Ikhsan, Muhammad; Abdillah, Luqmanul H.A; Sitorus, Patar Ariyanto; Pamungkas, Oky; Nurohman, Sabar (JURNAL EDUSCIENCE, 2024)
This study examines the profile of science process skills and scientific attitudes among students in Nunukan Regency. The study population includes 9th-grade students from junior high schools during the 2023/2024 school year. The research involved 243 students to evaluate science process skills and 332 students to assess scientific attitudes through questionnaires spanning 21 different schools. The research type is descriptive quantitative with the sampling technique being conducted through accidental sampling. The study administered 27 questions on electrical circuit material and a scientific attitude questionnaire with 40 statement items using a Likert scale. The results show that (1) varying levels of science process skills: observing (40%), classifying (39.4%), predicting (30.87%), planning experiments (40.6%), formulating hypotheses (40.2%), interpreting data (38.4%), implementing concepts (38.7%), measuring (37.3%), and communicating (36.2%). The average score for science process skills was 38%, falling into the low category. (2) In contrast, scientific attitude scores were higher: curiosity (71.3%), critical thinking (71.3%), respecting data/facts (63%), open-mindedness (74.1%), cooperation (68.1%), and honesty (72.2%), with an average score of 70%, falling into the high category. (3) The results of the correlation analysis indicate that H0 is rejected, and Ha is accepted. This means there is a significant relationship between scientific process skills and scientific attitude, which is weak but positive.